Modulation of gamma-band activity across local cortical circuits - Briggs, Farran; Usrey, Martin W. (Frontiers in Integrative Neuroscience, 2009)
Periodic activity patterns or oscillations within the gamma frequency band (20-80 Hz) have been implicated in sensory processing and cognition in many areas of the cerebral cortex, including primary visual cortex (V1). Although periodic activity appears to be a hallmark of cortical neurons, little is known about the dynamics of these activity patterns as signals progress within local cortical circuits. This study compares the strength of periodic activity between neurons in the input and output stages of cortical processing—neurons in layers 4 and 6—of V1 in the alert macaque monkey. Our results demonstrate that while both populations of neurons display significant gamma-band activity, this activity increases from the input to output layers of the cortex. These data suggest that local cortical circuits enhance periodic activity within a cortical area.